SUSTAINABLE URBAN WATERFRONT REDEVELOPMENT : CHALLENGE AND KEY ISSUES - Pramesti, Rochana Esti (MEDIA MATRASAIN, 2017)
Urban waterfronts as complex bioregions by nature and also socio-economical hubs by their history provide a real challenge for planning institutions in capturing and responding to the trends and dynamic of the development. In the perspective of being competitive, cities are exercising urban practises to attract investment and resources by rediscovering urban tradition and culture fundamental to build attractive urban identity. Tertiary industry including urban tourism is being developed in attractive and strategic places by revitalizing the city centre and the waterfronts.Understanding the challenge and key issues of urban waterfront redevelopment is crucial in the planning for sustainable future for the waterfront. This article descripts the challenge and issues found in the urban waterfront redevelopment; the problems that are integrally linked with the history of planning of the surrounding urban region, and the opportunity abound to be addressed as integral character of the city’s future growth. The approach to sustainable urban waterfront redevelopment differs from locale to locale, but the study cases show some challenge and key issues in the urban waterfront redevelopment are quite similar.Four cases of urban waterfront redevelopment plan located in Toronto Central Waterfront, Dalian Waterfront, Zanzibar’s Stone Town and Jakarta’s Waterfront are compared to understand the scope of the planning sector, the challenge characteristic to urban waterfront redevelopment, and the approach used in planning toward sustainable waterfront design. The objective of the case review is to find good examples of theory implementation : what are the destination of the future waterfronts, the planning approach and institutional and sectoral cooperations. The reason for choosing the cases is based on the difference of geographical location and culture, the difference approach and the possible difference of waterfront characteristic.  Zanzibar and Jakarta are located in developing countries and the two cases present a characteristic challenge; tackling urban problems including urban poverty as one of the main goals. Toronto and Dalian’s location in more developed world (Canada and China), provided some insight of difference and similarities with those in developing countries.The result shows that urban waterfront is indeed challenging environment where urban planning is constantly challenged by three pillar sectors; the economy, social and ecology. The evidence from case studies shows that major challenge found in the urban waterfront redevelopment should be addressed sustainably, requiring multi-sectoral and multi-scale institutional approach. Key issues and challenge in addressing urban waterfronts redevelopment include economic diversity, social identity, shifting land use made possible by urban policy, reconciling conflict of interests, local institutional capacity and the planning system and delivery mechanism implemented.Keywords : urban waterfront, sustainability, urban redevelopment, sustainable spatial planning